Scalar Disconnect: The logic of transboundary water governance in the Mekong - Suhardiman, Diana; Giordano, Mark; Molle, Francois (Informa UK Limited, 2012)
This article provides an institutional analysis of the Mekong River Commission and brings to light the institutional dissonances between regional and national decision-making landscapes in the Lower Mekong Basin. The current scalar disconnect between regional and national decision-making processes reflects how international donors and member country representatives obscure potential conflict/tension in transboundary water governance in the Mekong. From a scholarly perspective, it questions academic approaches that assume that the state is the sole or primary actor in international relations.